Multifunctional Hybrid Nanoparticles for Traceable Drug Delivery and Intracellular Microenvironment‐Controlled Multistage Drug‐Release in Neurons. Issue 20 (31st March 2017) - Shi, Bingyang; Du, Xin; Chen, Jian; Fu, Libing; Morsch, Marco; Lee, Albert; Liu, Yong; Cole, Nicholas; Chung, Roger
Abstract : Innovative nanoparticles hold promising potential for disease therapy as drug delivery systems. For brain‐disease therapy, a drug delivery system that can sustainably control drug‐release and monitor fluorescence of the drug cargos is highly desirable. In this study, a light‐traceable and intracellular microenvironment‐responsive drug delivery system was developed based on the combination of glutathione‐responsive autoflurescent nanogel, dendrimer‐like mesoporous silica nanoparticles, and gold nanoparticles. The resulting hybrid nanoparticles represent a new class of delivery system that can efficiently load, transport, and control multistage‐release of sulfydryl‐containing drugs into neurons, with light‐traceable monitoring for future brain‐disease therapy. Abstract : Gold‐functionalized dendrimer‐like silica‐nanogel hybrids are successfully designed and fabricated as light‐traceable and intracellular microenvironment‐responsive nanocarriers for smart sulfydryl‐containing drug delivery. The unique structure, large surface area, intracellular microenvironment‐responsive autofluorescence, and GSH‐triggered drug‐release render such nanocarriers as attractive for the delivery of sulfydryl‐containing drugs.